Excitation of parametric oscillations with random external signals - Titarenko, Alexander Myhailovych; Podhaiko, Oleh Ivanovych (НТУ "ХПІ", 2018)
Currently, the main technical means of communication systems are receiving and transmitting radio devices, which in their structure contain various converters and amplifiers operating in nonlinear modes. In the transmission paths themselves, interference, delays, mismatches and parametric effects can occur, which leads to the appearance of small amplitude signals in the information channels. These factors have a significant impact on the characteristics of the telecommunications system. Theoretical investigations of the influence of random signals (oscillations) on the operating modes of a nonlinear oscillatory system is an urgent task and aimed at expanding the possibilities of its use. In general, the analysis of random excitation of oscillations in nonlinear parametric systems is of interest for many branches of science and technology.

Теоретичні дослідження впливу випадкових сигналів (коливань) на режими роботи нелінійної коливальної системи є актуальним завданням і спрямовані на розширення можливостей її застосування. Взагалі, аналіз випадкового збудження коливань в нелінійних параметричних системах становить інтерес для багатьох галузей науки і техніки. В роботі проведено аналіз параметричних систем з суттєвою нелінійністю при наявності випадкових зовнішніх впливів. Розглянуті найбільш важливі випадки збудження індуктивної нелінійної системи. Отримані співвідношення, які надають можливість керувати параметрами перетвореного сигналу в залежності від режиму збудження.
Збудження параметричних коливань при випадкових зовнішніх сигналах
Keywords: nonlinear system; random signal; inductive circuit; theoretical investigations; нелінійна система; теоретичні дослідження